Diversity and public goods: A natural experiment with exogenous residential allocation - Yann Algan; Camille Hémet; David Laitin (Institute for the Study of Labor (IZA), 2011)
This paper demonstrates the effects of ethnic and religious diversity on the quality of public spaces. Its identification strategy relies on the exogeneity of public housing allocations in France, and thereby eliminates the bias from endogenous sorting. The paper uses micro evidence of social interactions within housing blocks from the representative French Housing survey, which allows for a detailed identification of the channels through which diversity operates. Differentiating among three channels of public goods provision, the paper finds that heterogeneity in the housing block leads to low levels of sanctions for anti-social behavior and low levels of collective action to improve housing conditions, but no losses in public safety.
urn:nbn:de:101:1-201111029392
Keywords: H10; H41; 330; fractionalization; public goods; collective action; discrimination; Ethnische Gruppe; Religion; Sozialstruktur; Diskriminierung; Wohnungsversorgung; Öffentliches Gut; Frankreich